Diagnóstico de la movilidad y seguridad peatonal en el sector calle 17 y carrera 24 con calle 17 vía Armenia en la ciudad de Pereira (2021)
This Degree Project is based on the elaboration of a diagnosis of mobility and pedestrian safety that aims to establish actions that allow protecting pedestrians who circulate through the corridors of the Calle 17 with coordinates (4 ° 48'04.18 "N 75 ° 41'39.87" W) and Carrera 24 with Calle 17 via Armenia with coordinates (4 ° 48'01.85 "N 75 ° 41'39.05" W), both being very busy pedestrian areas because they are close to Universities, terminal transport, La 14 shopping center; It also has a high traffic flow because it is a primary road that connects the cities of Pereira with Armenia.